Students’ Learning Styles in Blended English Learning in an Indonesian Private School - Husnia; Sahrir Nur; Amirullah Abduh (Naifaderu Cipta Sejahtera, 2023)
Purpose This research aimed at finding out the learning styles of Year 11 students of a private school in Makassar. The research particularly aims to explore students’ perception of Blended English Learning (BEL) and strategies in accommodating students’ learning styles. Methodology This research employed the explanatory sequential mixed-method design with quantitative and qualitative data. The participants consisted of 19 students and an English teacher. Data collection used some instruments, namely observation sheets, questionnaires, and semi-structured interviews. Results/Findings The results showed that the Year 11 students were dominated by auditory learning style with a minor preference category which means that the students used this learning style, but usually as a second choice or in conjunction with other learning styles. Next, the interview results revealed students’ views on the BEL differ according to their learning styles and most of them preferred face-to-face learning. Then, the findings on the teacher's observation and interviews showed that the teacher used differentiated strategy and thematic webbing. So, it helps him to implement different strategies for each student. Implications The results suggest that learning styles are the significant elements in the learning which help students achieve their learning goals. On this basis, this research will convey valuable information for future research that will explore the students' learning styles in a private school.